ELECTROCHEMICAL PERFORMANCES AND CORROSION INHIBITION OF AA6061 IN TROPICAL SEAWATER - R. Rosliza; H.B. Senin; W.B. Wan Nik (Universitas Gadjah Mada, 2008)
The corrosion performances of AA6061 aluminum alloy in tropical seawater was investigated using potentiodynamic polarization, electrochemical impedance spectroscopy (EIS) and their morphology was characterized by the scanning electron microscopy (SEM). The results showed that the presence of sodium benzoate as an inhibitor significantly decrease the corrosion current densities (i corr ), corrosion rates and double layer capacitance (C dl ), whilst increasing the polarization resistance (R p ). The scanning electron microscopy (SEM) images indicated that the mechanism of charge transfer and the formation of thin film have been taken place on the specimens.